‚Nützliches‘ Wissen in der wissenschaftlichen Politikberatung?: Ein linguistisch-erkenntnistheoretisches Projekt - Janine Gondolf; Armin Grunwald; Dorothee Jahaj; Nina Janich (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis, 2023)
Scientific policy advice is a special, hybrid type of scientific activity: science in its advisory function faces the conflict of having to present content in a scientifically credible, unbiased, and value-free form and, at the same time, to prepare it in a politically effective way, i.e., in a way that guides action and is publicly comprehensible. The resulting texts are therefore particularly interesting for approaching scientific research practices with regard to the question of how the struggle for epistemic quality and social legitimacy is reflected in their language and content in the (co-)construction of knowledge. Using exemplary cases, a current interdisciplinary DFG project investigates the practice of scientific policy advice in Germany in terms of form, content, and function from a linguistic and epistemological perspective.